2022
DOI: 10.1021/acsbiomedchemau.2c00016
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated Characteristics of a Selective, Potent Neuromedin-U Receptor 2 Agonist

Abstract: Neuromedin-U (NMU) mediates several physiological functions via its two cognate receptors, NMUR1 and NMUR2. Disentangling the individual roles of each receptor has largely been undertaken through the use of transgenic mice bearing a deletion in one of the two receptors or by testing native molecules (NMU or its truncated version NMU-8) in a tissuespecific manner, in effect, taking advantage of the distinct receptor expression profiles. These strategies have proved quite useful despite the inherent limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One previous study has identified TPH2 and NMU as neuropeptides that suppress appetite 45 . Neuromedin U was initially isolated from porcine spinal cord and subsequently found in mammals, 46 birds, 22 amphibians, 47 and fish 48 . It may exert anorexic effects by upregulating corticotropin‐releasing hormone and arginine‐angiotensin in the central nervous system 49 .…”
Section: Discussionmentioning
confidence: 99%
“…One previous study has identified TPH2 and NMU as neuropeptides that suppress appetite 45 . Neuromedin U was initially isolated from porcine spinal cord and subsequently found in mammals, 46 birds, 22 amphibians, 47 and fish 48 . It may exert anorexic effects by upregulating corticotropin‐releasing hormone and arginine‐angiotensin in the central nervous system 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In human innate immunity, it is possible that disruption of the NMU pathway would lead to protection from WNV infection in pancreatic β-cells and other cell types, as well as other mammalian models. A known antagonist of NMU signaling has been identified [ 74 ]. However, disruption of NMU activity may have adverse side effects.…”
Section: Discussionmentioning
confidence: 99%